Securing mobility in Bucaramanga: Road safety control based on a mobile application - Angarita Reina, Fredy; Aparicio Durán, Brayan Alfonso; Arias Quintero, Pedro Alberto; Gómez Salgado, Luis; Gil Herrera, Richard de Jesús; Delgado, Daniel Ricardo (Ingeniería Solidaria, 2024)
Introduction: The smart city paradigm is made up of a set of actors who must operate jointly to guarantee road flow. However, sometimes there are accidents, and they affect productive apparatus, cause minor or temporary injuries and sometimes death of the individuals involved.Problem: Events occur for multiple reasons and the authorities have difficulties in implementing controls that minimize their occurrence since they do not have the necessary tools to capture and analyze timely information on the claims that have been presented.Objective: The objective is to increase road safety control and safeguard mobility in Bucaramanga. For this, a mobile application is designed to capture accident data by implementing the Flutter framework and the Model-View design pattern methodology. Controller (MVC).Methodology: The development of software to analyze the large amount of information on road events. A database is developed where said information is stored and processed using programming languages, coding and data hosting. Design and process factors are also considered according to the user’s needs, which will determine the interface and expected performance.Results: A structured system for data capture with the ability to integrate the general community, streamline the availability of information and facilitate decision making that deals with the problem in real time.Conclusion: It is concluded that its implementation in the city fosters self-care for pedestrians and drivers, facilitating the design of effective control measures by territorial entities, bringing the city of Bucaramanga closer to sustainability.Originality: This methodology for integrating events is unique in the country and is developed based on the city’s own characteristics.Limitations: The lack of information provided by the government actors.
Keywords: Road accidents; road safety; mobility; sustainability; information / data management; App Development